The Impact of Foreign Languages in Social Culture Scope on Technology and Vocational Education in Indonesia - Muhammad Sadam Rizkylillah Rizkylillah; Rafida Sahartaqiya; Aghnina Camilla Husna; Suyitno Muslim; Wisnu Djatmiko (Universitas Islam Tribakti Lirboyo Kediri, 2024)
In the era of globalization, the flow of cultural, informational, and technological exchanges underscores the importance of mastering foreign languages as a tool for cross-national communication. In Indonesia, proficiency in foreign languages has become increasingly relevant, especially in supporting the development of technological and vocational education. As foreign languages dominate various aspects of life, the rich local culture with its traditional values risks being marginalized. This phenomenon is particularly evident in the education sector, where many students prioritize foreign language proficiency to meet the demands of the global labor market while understanding local socio-cultural values becomes increasingly neglected. This study aims to find strategic solutions to integrate foreign language proficiency without compromising the nation's socio-cultural identity in technological and vocational education. The research method used is a literature review with a descriptive qualitative approach. Data collection was conducted through web and metadata search applications for research articles. Data analysis followed the Miles & Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the interaction between socio-cultural factors, including foreign language skills, has a significant impact on the development of technological and vocational education in Indonesia. The implications of this study recommend that policymakers give substantial attention to these factors to enhance technological and vocational education rather than hinder it.